Resistance of Cucurbita maxima to Phytophthora capsici - Brune, Sieglinde; Lopes, José Flávio (Pesquisa Agropecuaria Brasileira, 1994)
Phytophthora capsici causes damping-off and the disease is a growing concern in squash planting fields, since it has been showing a rising incidence. In order to evaluate the germplasm collection of the National Center for Vegetable Crops Research (CNPH), in Brasília, DF, Brazil, and identify sources of resistance, 156 Cucurhita maxima genotypes were planted in the first year and the 51 which presented surviving plants, were planted in the second year. The fungus was inoculated by spraying a zoospore suspension at the stem basis. In the first year, the surviving rate varied from 0 to 91% and; in the second year, from 0 to 100%. Genotypes 172, 179, 032, 076 and 077 showed the best performance, varying from 37 to 91% of surviving plantlet rates, in the first year. In the second year, genotypes 179 (SIB and SP), 127 (SIB), 400 (SP), 177 (OP) and 172 (SIB and SP) showed the highest rates with 90% or more of surviving plantlets.